Cocaine Rituals in Club Culture: Intensifying and Controlling Alcohol Intoxication - Edland-Gryt, Marit (Journal of drug issues, 2021)
Clubbing is an important part of the nighttime economy, and cocaine use is, for some young people, an essential part of this clubbing culture. However, the interaction rituals around the use of powder cocaine in this context remain understudied. This study is based on qualitative interviews with young adult recreational cocaine users (n = 28) and explores how they use cocaine in club settings, in relation to rituals and drinking culture. The analysis identified three main explanations for using cocaine: (a) unity with friends because of shared transgression, (b) the high as a “collective effervescence,” and (c) the possibility to control, extend, and intensify drinking to intoxication. These three explanations illustrate how cocaine rituals were deeply integrated in drinking-to-intoxication rituals, and how the illegality of cocaine use reinforced feelings of unity with friends. In the nighttime economy, cocaine use and its related rituals are used to intensify and control alcohol-fuelled partying.